Multi-product Firms and Product Basket Adjustments in Ethiopian Manufacturing - Admasu Shiferaw (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
This paper analyzes firm level adjustment of the product mix and its implications for aggregate output growth. Using firm level panel data from Ethiopian manufacturing during the period 1996-2007, it shows that about 30% of firms adjust their 'extensive margin' annually by adding and/or dropping at least one product and about half of those firms undertake such adjustment only through product adding. At the aggregate level, about 30% of annual growth in sales is accounted for by the adjustment of the extensive margin which is more than four times the net contribution of firm entry and exit. The paper also shows that the likelihood of adding a product tends to decline with firm size and increases dramatically with the incidence of large investment outlays. While the level of productivity does not seem to increase the probability of adding a product, a net increase in the number of products is strongly associated with subsequent growth in sales, productivity and capital stock at the firm level.
Keywords: D21; E23; L11; L60; 330; Product Switching; Multiproduct Firms; Extensive Margin; Intensive Margin; Ethiopian Manufacturing